4(y+3)=3(5y-7)

Simple and best practice solution for 4(y+3)=3(5y-7) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(y+3)=3(5y-7) equation:


Simplifying
4(y + 3) = 3(5y + -7)

Reorder the terms:
4(3 + y) = 3(5y + -7)
(3 * 4 + y * 4) = 3(5y + -7)
(12 + 4y) = 3(5y + -7)

Reorder the terms:
12 + 4y = 3(-7 + 5y)
12 + 4y = (-7 * 3 + 5y * 3)
12 + 4y = (-21 + 15y)

Solving
12 + 4y = -21 + 15y

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '-15y' to each side of the equation.
12 + 4y + -15y = -21 + 15y + -15y

Combine like terms: 4y + -15y = -11y
12 + -11y = -21 + 15y + -15y

Combine like terms: 15y + -15y = 0
12 + -11y = -21 + 0
12 + -11y = -21

Add '-12' to each side of the equation.
12 + -12 + -11y = -21 + -12

Combine like terms: 12 + -12 = 0
0 + -11y = -21 + -12
-11y = -21 + -12

Combine like terms: -21 + -12 = -33
-11y = -33

Divide each side by '-11'.
y = 3

Simplifying
y = 3

See similar equations:

| t^2-3t-18= | | x^2-5c=-6 | | 5(h+4)=8 | | 4.5x+12.5y=4500 | | .25x^2-.0833x-.166=0 | | 6=-2(7-l) | | 12=-4(-6-3x) | | 2(x-6)=24 | | 3x-x+3=7 | | 3a-7=5(2a-3)+4 | | 2w^2-3w+35=0 | | 6(2n-5)+16=10n-18 | | -4(d+5)+10=-5 | | -(12k-11)=7 | | -7m-m^2=0 | | 8.1+3.9h-5.6h=-7.2 | | 7x^2-41x-56= | | 2w-15=43 | | 0.02x+0.9+0.04x=0.02 | | 5(3c-7)=13(c+3) | | 3[(20-7)+1]= | | 38+2v=8(1-6v) | | 3k-8=5k | | -3(x+6)= | | -(-4-6x)=10 | | 2x+100=600 | | x*x+8+3x+6=24 | | -12=5v+2v | | 4x(x+2)=2x+10 | | 9p^2-40q^2= | | 16x-x^2=0 | | X*X+8+3X+6= |

Equations solver categories